Refining the Typical Scenarios by Additional Factors - Kuzminykh, V.O.; Koval, O.V.; Otrokh (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2020)
The problems in the quality assessment modeling scenarios collecting information flow on an extensive network of the example of the problem of building and further optimization scenarios to analyze the budget process on an extensive network. Shown use structured approach to the ontology as considered most appropriate to the task of presenting the structure as a graph. Moved assessment of the effect of the use of partial information previously obtained by constructing scenarios collecting information flow on the network, described the count, with further refinement information. An formalized description of the hierarchical structure of the system. An example of the structure of the interaction of ontology elements for the problem of budget analysis is presented. У роботі розглянуті задачі оцінки якості моделювання сценаріїв збору потокової інформації на розгалуженій мережі на прикладі задачі побудови та подальшої оптимізації сценаріїв для аналізу бюджетного процесу на розгалуженій мережі. Показано використання структурного підходу до розгляду онтології, як найбільш відповідного до розглянутої задачі, з представленням структури у вигляді графу. Переведено оцінку ефекту від використання раніше отриманої часткової інформації по побудові сценаріїв збору потокової інформації на мережі, що описується графом, при подальшому уточненні інформації. Наведено формалізований опис ієрархічної структури системи. Представлено приклад структури взаємодії елементів онтології для задачі бюджетного аналізу.